Natural bioactive flavonoids as promising agents in alleviating exercise-induced fatigue. (February 2023) - Liu, Yuzhou; Shen, Xiaofei; Sha, Mengxiang; Feng, Zige; Liu, Yue
Abstract: Exercise-induced fatigue is a common phenomenon caused by prolonged strenuous exercise and physical labor as a feeling of exhaustion and reduction of muscle performance, which seriously affects people's health, work efficiency and quality of life. Meanwhile, numerous studies have shown that natural flavonoids can be an excellent source for preventing and treating exercise-induced fatigue due to their extraordinary antioxidant and anti-inflammatory properties. However, the review of flavonoids in alleviating exercise-induced fatigue is still limited. Therefore, this review systematically summarizes recent studies on natural bioactive flavonoids that can alleviate exercise-induced fatigue and improve physical performance, including their plant sources, structure types and features, pharmacological effects and underlying mechanisms against exercise-induced fatigue. Also, the clinical trials have also been reviewed. Flavonols, isoflavones, anthocyanins, and their corresponding glycosides are the major bioactive flavonoids in alleviating exercise-induced fatigue. The current data and the further molecular docking evidently support the potential anti-fatigue effects of these flavonoids mainly involving the inhibition of oxidative stress and inflammatory response, as well as the regulation of energy metabolism. Activation of the Keap1/Nrf2/ARE and AMPK/PGC1-α pathways are responsible for the improvement of flavonoids against exercise-induced fatigue. Hence, this review is expected to contribute to the further research and development of anti-fatigue flavonoids in the functional food and nutraceutical industry. Graphical abstract: Image 1 Highlights: Antioxidant activity of flavonoids is crucial in relieving exercise-induced fatigue. Flavonoids improve anti-inflammation activity and regulate energy metabolism system. Flavonoids are expected as promising exercise-induced fatigue-alleviating agents.